Effectiveness of a Multimodal, Day Clinic Group-Based Treatment Program for Trauma-Related Disorders: Differential Therapy Outcome for Complex PTSD vs. Non-Complex Trauma-Related Disorders - Philipps, Anke; Silbermann, Andrea; Morawa, Eva; Stemmler, Mark; Erim, Yesim (Frontiers in Psychiatry, 2019)
Background: The effectiveness of the psychotherapeutic treatment of posttraumatic stress disorder is evidence-based and generally considered proven. However, the effectiveness of multimodal, group-based day clinic treatment programs has rarely been investigated. Moreover, there is no consensus in the literature concerning the question whether psychotherapeutic approaches for trauma-related disorders are also applicable for patients with complex PTSD (cPTSD). The aim of the study was to evaluate our multimodal group-based treatment program regarding a change of psychiatric burden, a change of protective factors and possible differences in therapy outcome for patients with or without cPTSD. Methods: Our group-based treatment for patients with trauma-related disorders was examined in 66 patients who filled out the following questionnaires in the first and in the last week of treatment: Essen Trauma Inventory (ETI), Screening for complex PTSD (SkPTBS), Patient Health Questionnaire- somatization module (PHQ-15), Beck Depression Inventory-Revised (BDI-II), Posttraumatic Growth Inventory (PTGI) and Questionnaire on social support (F-SozU). Results: The treatment was shown to significantly reduce depressive symptoms (p < 0.001, d = -0.536) and increase posttraumatic growth (New Possibilities: p = 0.004, d = 0.405; Personal Strength: p = 0.005, d = 0.414). For patients with cPTSD, depressive (p = 0.010, d = -0.63) as well as cPTSD symptoms (p = 0.020, d = -0.796) were significantly reduced, perceived social support was increased after day clinic treatment (p = 0.003, d = 0.61). Contrary to our expectations, somatoform symptoms were increased after therapy. Conclusions: The present work expands previous research by demonstrating that multimodal group-based, day clinic treatment is effective in the treatment of trauma-related disorders, also in its complex form.